Factors that influence the customer's satisfaction towards the pharmaceutical service quality: a case study of Hospital Sultan Abdul Halim, Sungai Petani Kedah / Mohammad Raffi Fhidzon - Fhidzon, Mohammad Raffi (2017)
The purpose of this study is to determine the factors that influence the customer's satisfactions towards pharmaceutical service quality in Hospital Sultan Abdul Halim. The research executed was to test the relationship between five criteria which are service promptness, pharmacist attitude, medication counseling, pharmacy facilities, and pharmacy location with customer's satisfactions towards the pharmaceutical service quality. A survey to all 100 respondents was conducted at Hospital Sultan Abdul Halim's Pharmacy which is located in Jalan Lencongan Timur, Bandar Amanjaya, 08000 Sungai Petani Kedah. The result for this study has been analyzed using Statistical Package for the Social Sciences (SPSS). By having a better understanding of the influence of customer's satisfactions for the pharmaceutical service quality, the pharmaceutical industry especially the Hospital Sultan Abdul Halim's Pharmacy would have a brand new marketing strategies and massive improvements on customer services to attract larger groups and distinctive layer of customers.